(untitled) (Scientific journal of the Fergana State University, 2026)
The article systematically analyzes the taxonomy of birds permitted for hunting in Uzbekistan by classes, orders, families and species. As a result of the research, 8 orders, 12 families and 45 species of birds permitted for hunting in Uzbekistan were identified. When studying the distribution features of game birds officially permitted for hunting in Uzbekistan, in the Bukhara region, out of 45 species, 42 were registered in the nature of the region. The purpose of our research work is to study the "fauna, ecology and importance of game species in the desert zone of Uzbekistan." Today, special attention is paid to the protection and rational use of wildlife, which is an important component of global biodiversity. In particular, the widespread and sometimes irrational use of wild animals for hunting purposes, as well as existing problems in the field of hunting, in many cases lead to the disappearance or reduction in the number of species, sometimes turning them into rare or endangered species.